Education for "motherhood": a case study on the subjectivities of the women participating in the mother-child education program - Bayraktar, Sevi. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
This study aims to analyze the subjectivity formations of the urban to rural migrant women who are subjected to the education programs on ‘motherhood’. Among the variety of Non-Governmental Organizations (NGOs) the focus of this study is on the Mother-Child Education Program (AÇEP) of the Mother-Child Education Foundation (AÇEV), which is a private foundation working with the state institutions collaboratively. In this regard, this thesis examines the operations of the ‘Education for Motherhood’ Program in one of the politically marginalized and economically deprived areas of stanbul, the Gazi neighborhood, and tries to comprehend its ‘reflections’ in everyday life experiences of the women with whom the actors of state and civil society attempted to make ‘proper’ mothers. In this process, through a fantasy of modern, middle-class womanhood, as the model of ‘proper’ mothering, the working class women living in the Gazi neighborhood are alienated to their class positions, ethnic identities and the ways of gender-based oppression within the patriarchal social structure. In fact, this study tries to display how power operates in the ‘gap’ between the fantasy of middle-class nuclear family and the actuality of the everyday life conditions of the marginalized inhabitants of the Gazi neighborhood. To this extent, while women become the agents of the state at home and the mediators of its operations in the neighborhood they use various "tactics" around this ‘gap’ and play with different subject positions to have "agency" in the face of the power-holder actors both in the private and the public spaces.
Keywords: Education, Preschool -- Turkey.; Mother and child -- Turkey.